Pneumococcal Meningitis Outbreaks in Africa, 2000–2018: Systematic Literature Review and Meningitis Surveillance Database Analyses. (1st September 2021) - Franklin, Kat; Kwambana-Adams, Brenda; Lessa, Fernanda C; Soeters, Heidi M; Cooper, Laura; Coldiron, Matthew E; Mwenda, Jason; Antonio, Martin; Nakamura, Tomoka; Novak, Ryan; Cohen, Adam L
Abstract: Background: The meningitis belt of sub-Saharan Africa has traditionally experienced large outbreaks of meningitis mainly caused by Neisseria meningitidis . More recently, Streptococcus pneumoniae has been recognized as a cause of meningitis outbreaks in the region. Little is known about the natural history and epidemiology of these outbreaks, and, in contrast to meningococcal meningitis, there is no agreed definition for a pneumococcal meningitis epidemic. The aim of this analysis was to systematically review and understand pneumococcal meningitis outbreaks in Africa between 2000 and 2018. Methods: Meningitis outbreaks were identified using a systematic literature review and analyses of meningitis surveillance databases. Potential outbreaks were included in the final analysis if they reported at least 10 laboratory-confirmed meningitis cases above baseline per week with ≥50% of cases confirmed as pneumococcus. Results: A total of 10 potential pneumococcal meningitis outbreaks were identified in Africa between 2000 and 2018. Of these, 2 were classified as confirmed, 7 were classified as possible, and 1 was classified as unlikely. Three outbreaks spanned more than 1 year. In general, the outbreaks demonstrated lower peak attack rates than meningococcal meningitis outbreaks and had a predominance of serotype 1. Patients with pneumococcal meningitis tended to be older and had higher case fatality rates than meningococcal meningitis cases. An outbreak definition, which includes a weekly district-level incidence of at least 10 suspected cases per 100 000 population per week, with >10 cumulative confirmed cases of pneumococcus per year, would have identified all 10 potential outbreaks. Conclusions: Given the frequency of and high case fatality from pneumococcal meningitis outbreaks, public health recommendations on vaccination strategies and the management of outbreaks are needed. Improved laboratory testing for S. pneumoniae is critical for early outbreak identification.